Anti-miRNA oligonucleotides: A comprehensive guide for design. Issue 3 (4th March 2018) - Lima, Joana Filipa; Cerqueira, Laura; Figueiredo, Ceu; Oliveira, Carla; Azevedo, Nuno Filipe
ABSTRACT: MicroRNAs (miRNAs) are small, non-coding RNA molecules that regulate gene expression post-transcriptionally. As a consequence of their function towards mRNA, miRNAs are widely associated with the pathogenesis of several human diseases, making miRNAs a target for new therapeutic strategies based on the control of their expression. Indeed, numerous works were published in the past decades showing the potential use of antisense oligonucleotides to target aberrant miRNAs (AMOs) involved in several human pathologies. New classes of chemical-modified-AMOs, including locked nucleic acid oligonucleotides, have recently proved their worth in silencing miRNAs. A correct design of a specific AMOs can help to improve their performance and potency towards the target miRNA by increasing for instance nuclease resistance and target affinity. This review outlines the technologies involved to suppress aberrant miRNAs. From the design strategies used in AMOs to its application in novel miRNA-based therapeutics and detection methodologies.